Imiquimod-induced colitis: A novel ROS/ERK-driven model of intestinal inflammation and barrier dysfunction - Kuang-Ting Liu; Shu-Hao Chang; Kuan-Chen Wu; Zheng-Yi Li; Mao-Chia Chang; Yen-Chu Huang; Mu-Chi Chung; Shih-Chung Wang; Yi-Ju Chen; Jeng-Jer Shieh (Chemico-Biological Interactions, 2026)

Integrated Multi-Endpoint Analysis of Soluble Copper(II) Chloride–Induced Oxidative Stress, Mitochondrial Dysfunction, and Genotoxicity in RAW264.7 Macrophages - Ping-Kun Tsai; Sheng-Wen Wu; Yen-Ju Lee; Yu-Ting Chang; Shiuan-Shinn Lee; Yung-Chuan Ho; Li-Chiu Yang; Yu-Hsiang Kuan (Biological Trace Element Research, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Palladium-catalyzed thermo, photo, and electrocatalytic CO₂ conversion to methanol and formaldehyde: A review of mechanistic pathways using synthetic, biogas, and fossil-derived CO2 - Yen-Yi Lee; Masimukku Srinivaas; I.-Cheng Li; Kapa Keharika; Rajender Boddula; Ramyakrishna Pothu; Sanna Gull; Bo-Wun Huang; Jein-Wen Chen; Prashanth W. Menezes; Guo-Ping Chang-Chien (Journal of Environmental Chemical Engineering, 2025)

CuO/PVA-based ultra-low-volume oral H2S detection system to reveal tongue coating effects - Moumita Deb; Chang-Chuan Huang; Yen-Ming Lai; Chang-Ju Chu; Yu-Shan Lee; Chien-Ting Chen; William Lee; Hsin-Fei Meng; Li-Yin Chen; Olivier Soppera; Chao-Sung Lai; Ding-Han Wang; et al. (Chemical Engineering Journal, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Unraveling urban plant diversity: The independent effects of plant species richness and greenness on health - Chia-Ching Wu; Chun-Yen Chang; Brian Deal; Dongying Li; William C. Sullivan (Urban Forestry & Urban Greening, 2025)

Fermented Soybean Pulp Alleviates Disease Progression of 5×FAD Model Mice - Chun-Yen Yang; Yu-Hsuan Liu; Ta-Chun Lin; Kuo-Hsuan Chang; Hsiu Mei Hsieh-Li (Molecular Neurobiology, 2025)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder of the central nervous system, characterized by memory loss and cognitive decline. The two main hypotheses regarding AD involve the accumulation of amyloid-β (Aβ) forming plaques and the intracellular hyperphosphorylation of tau protein, leading to the formation of neurofibrillary tangles (NFT). These processes are accompanied by neuroinflammation and oxidative stress, and eventual neuronal death. While soy foods are widely recognized for their nutritional benefits, soybean pulp (okara), the residue left over from making tofu or soybean milk, is mostly discarded as kitchen waste, despite being rich in nutrients such as dietary fiber, protein, and isoflavones. This underutilized byproduct may serve as a valuable resource for functional food development and sustainable resource use. In this study, fermented soybean pulp (FS) demonstrated neuroprotective effects. In vitro, FS at concentrations of 0.001 µg/mL and 0.01 µg/mL significantly improved cell viability in Aβ-induced HT-22 cells and reduced lipid peroxidation. Further, in vivo oral administration of FS attenuated the cognitive deficits of 5 × FAD mice, enhancing both short and long-term memory and reducing anxiety-like behaviors. Immunohistochemical analysis revealed that the FS-treated 5 × FAD mice group significantly reduced hippocampal amyloid plaque accumulation and gliosis. FS also upregulated the expression levels of brain-derived neurotrophic factor (BDNF), PSD95, and synaptophysin, while preventing hippocampal neuronal loss. Mechanistically, FS may activate the Nrf2 antioxidant pathway and NF-κB-mediated inflammation through the modulation of the Akt/GSK3β signaling axis in the hippocampus. These molecular actions likely contribute to increased antioxidant enzymes and suppressed neuroinflammatory responses. Overall, this study suggests that FS has therapeutic potential for alleviating cognitive and behavioral impairments in AD. Moreover, the repurposing of soybean pulp, which would otherwise be discarded, enhances its utilization value and supports sustainable green recycling.

A steroid-rich fraction from parasitic climber Cocculus hirsutus (L.) W.Theob inhibits coronavirus disease and neutrophilic inflammation - Vidya Febrasca Tenderly; Thiyagarajan Raviraj; Yen Chi Loo; Olha Mykhailenko; Marcela Safratova; Stefan Kosturko; Mahendra Jadhao; Yu-Li Chen; Tsong-Long Hwang; Fang-Rong Chang; Michal Korinek (Phytochemistry Letters, 2025)

Chlamydia trachomatis disrupts host metabolism in primary cervical epithelial cells - Heng Choon Cheong; Muhammad Ihsan Rommel; Yi Ying Cheok; Yee Teng Chan; Ting Fang Tang; Sofiah Sulaiman; Chung Yeng Looi; Bernard Arulanandam; Li-Yen Chang; Won Fen Wong (World Journal of Microbiology and Biotechnology, 2025)

Ice ball size and temperature change during cryoablation in a lard and an ethiodized-oil tissue phantom - Nai-Wen Chang; Shu-Huei Shen; Chien-An Liu; Felix Antony Halim; Jia-An Hong; Chih-Chien Li; Ping-Lang Yen (Cryobiology, 2025)

Research note: assessing human preferences for natural landscapes—an analysis of ChatGPT-4 and LLaVA models - Yu-Hsin Tung; Zhe-Rui Yang; Meng-Wei Shen; Chun-Yen Chang; Chien-Chung Chen; Li-Chih Ho (Landscape and Urban Planning, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

Advanced ceramic membranes: Novel strategies for sulfamethoxazole removal in wastewater treatment - Yen-Yi Lee; Guo-Ping Chang-Chien; I.-Cheng Li; Bo-Wun Huang; Minh-Ky Nguyen; Minh-Thuan Pham; Chien-Hsing Wu (Journal of Environmental Chemical Engineering, 2024)

Crystal orientation control in angstrom-scale channel membranes for significantly enhanced blue energy harvesting - Chia-Hui Chuang; Yu-Hsiang Peng; Chung-Kai Chang; Po-Ya Chang; Dun-Yen Kang; Li-Hsien Yeh (Chemical Engineering Journal, 2024)

Investigation of verapamil-induced cardiorenal dysfunction and compensatory ion regulation in zebrafish embryos - Jiun-Lin Horng; Bu-Yuan Hsiao; Wen-Ting Lin; Tzu-Ting Lin; Ching-Yen Chang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

High-spatiotemporal-resolution PM2.5 forecasting by hybrid deep learning models with ensembled massive heterogeneous monitoring data - Kuan-Yen Wu; I-Wen Hsia; Pu-Yun Kow; Li-Chiu Chang; Fi-John Chang (Journal of Cleaner Production, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

A step closer to the convention on the Protection of Underwater Cultural Heritage 2001: China’s latest efforts in regulation - Xintong Li; Yen-Chiang Chang (Marine Policy, 2023)

The effect of environmental factors on spatial-temporal variation of heterobranch sea slug community in northern Taiwan - Ho Yeung Chan; Yen-Wei Chang; Li-Shu Chen; Kazuki Nishida; Yi Ta Shao (Frontiers in Marine Science, 2022)
Sea slug (Subclass Heterobranchia) biodiversity is an important element of marine coral reef communities. However, due to their small size and cryptic behavior, few studies have examined their spatiotemporal variation. Taiwan is in the middle of East Asia Island Arcs, where it is one of the hotspots of sea slug diversity. Meanwhile, the northeast coast of this island lies within the subtropical monsoon region, where the climate shifts from a warm southwest monsoon (SW: May to Sep) to a cold northeast monsoon (NE: Oct to Apr). Between the monsoons, distinct temperatures and currents result in different community structures. To understand how those environmental factors (i.e., monsoon season, diel period and water depth) influence sea slug species richness and assemblages, we surveyed these invertebrates monthly at both night and day by diving in a marine protection area (CJ) and at a nearby non-protected site (MR) from May 2020 to Apr 2021. We showed that the species composition in our sampling area was highly consistent with what was found in Okinawa and Pescadores island, but less similar to those in southern Taiwan or Hong Kong. On the northeast coast of Taiwan, sea slug number and abundance were both higher in CJ than MR, but biodiversity ( H’ ) and the species evenness index J ’ was lower in CJ than MR. Additionally, cluster analysis indicated that the sea slug assemblages differed between the two sites. Monsoon season significantly influenced both species richness and species assemblages, with species richness during SW being significantly higher than in the NE monsoon and species assemblages also being distinct between these two seasons. Moreover, species richness increased with water depth (within the surveyed range of 0-25 m). Diel period did not exert a strong impact on sea slug biodiversity, except for species richness at CJ, where it was higher during the day than at night. Our study suggested that changing currents between the monsoon seasons could transport individuals originating from either the north or south of these island arcs. Furthermore, temperature and food sources may differ between seasons and depths, thereby influencing sea slug assemblages in this region.

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Activation of multiple proteolysis systems contributes to acute cadmium cytotoxicity - Yen-Hsiu Yeh; Chia-Chih Tsai; Tien-Wen Chen; Chieh-Hua Lee; Wei-Jer Chang; Mei-Yi Hsieh; Tsai-Kun Li (Molecular and Cellular Biochemistry, 2022)

Exploring the Deeper Crustal Structure Beneath the Tatun Volcanic Area, Taiwan - Chien-Min Su; Wei-Jhe Wu; Strong Wen; Yi-Heng Li; Yen-Che Liao; Wen-Yen Chang; Chau-Huei Chen (Pure and Applied Geophysics, 2021)

The Impact of “Belt and Road Initiative” on Japanese Shipping Law - Yen-Chiang Chang; Bin Xu; Shuo Li (Coastal Management, 2021)

Relationships among cigarette smoking, urinary biomarkers, and urothelial carcinoma risk: a case-control study - Chi-Jung Chung; Hui-Tsung Hsu; Chao-Hsiang Chang; Sheng-Wei Li; Chiu-Shong Liu; Mu-Chi Chung; Guo-Wei Wu; Wei-Ting Jung; Yen-Jung Kuo; Hui-Ling Lee (Environmental Science and Pollution Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Comprehensive Natural Environment and Landscape Signs in Coastal Settlement Hazard Assessment: Case of East Taiwan between the Coastal Mountain and the Pacific Ocean - Shyang-Woei Lin; Chia-Feng Yen; Chih-Hsin Chang; Li-Jin Wang; Hung-Ju Shih (Journal of Marine Science and Engineering, 2020)
In East Taiwan, coastal settlements are scattered and narrowly confined between the Coastal Mountain and the Pacific Ocean. These settlements are currently at risk as there is no room for retreat. Therefore, it is essential to conduct a comprehensive and continuous hazard assessment in these coastal residential areas. In order to avoid biased towards the natural environment, the factors that cannot easily be built within the geographic information system (GIS) database are distinguished by Unmanned Aerial Vehicle (UAV) to conduct a vulnerability assessment of threats to coastal zones. The method: we used the east coast of Taiwan as an example, through GIS and statistical analysis in land-use status, vulnerable population groups and UAV landscape signs of indicators of erosion and accumulation. Through the main output of an intuition scatter map, the erosion landscape susceptibility, economical land-use exposure, and special population groups’ ratio allowed for the easy comparison of the vulnerability, risk level and resilience between different coastal settlements. These diverse observation aspects of risk assessment results can provide prevention and control strategies that meet the different needs of coastal risk management in restricting and strengthening the land-use development of communities.

Computational comparison of bone cement and poly aryl-ether-ether-ketone spacer in single-segment posterior lumbar interbody fusion: a pilot study - Chih-Wei Chang; Yu-Hsuan Chung; Chia-Jung Chang; Yen-Nien Chen; Chun-Ting Li; Chih-Han Chang; Yao-Te Peng (Physical and Engineering Sciences in Medicine, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Chemical characteristics, source apportionment, and regional transport of marine fine particles toward offshore islands near the coastline of northwestern Taiwan Strait - Cheng-Chih Chang; Chung-shin Yuan; Tsung-Chang Li; Yen-Lung Su; Chuan Tong; Shui-Ping Wu (Environmental Science and Pollution Research, 2018)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Oral vaccine of Lactococcus lactis harbouring pandemic H1N1 2009 haemagglutinin1 and nisP anchor fusion protein elevates anti-HA1 sIgA levels in mice - Stella Siaw Xiu Joan; Jee Pui-Fong; Adelene Ai-Lian Song; Li-Yen Chang; Khatijah Yusoff; Sazaly AbuBakar; Raha Abdul Rahim (Biotechnology Letters, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Granger causality-based synaptic weights estimation for analyzing neuronal networks - Pei-Chiang Shao; Jian-Jia Huang; Wei-Chang Shann; Chen-Tung Yen; Meng-Li Tsai; Chien-Chang Yen (Journal of Computational Neuroscience, 2015)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Reconstruction of nerve root sheaths for sacral extradural spinal meningeal cysts with spinal nerve root fibers - JianJun Sun; ZhenYu Wang; ZhenDong Li; HaiBo Wu; RuYu Yen; Mei Zheng; Qing Chang; Isabelle Yisha Liu (Science China Life Sciences, 2013)

Mechanism of Two Novel Human GJC3 Missense Mutations in Causing Non-Syndromic Hearing Loss - Ching-Chyuan Su; Shuan-Yow Li; Yung-Chang Yen; Jhih-Hao Nian; Wei-Guang Liang; Jiann-Jou Yang (Cell Biochemistry and Biophysics, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

3D Micro-Crack Propagation Simulation at Enamel/Adhesive Interface Using FE Submodeling and Element Death Techniques - Heng-Liang Liu; Chun-Li Lin; Ming-Tsung Sun; Yen-Hsiang Chang (Annals of Biomedical Engineering, 2010)

Exploring Taiwanese teachers’ perceptions toward and knowledge of climatic hazard mitigation - Chun-Yen Chang; Ying-Lin Chen; Chia-Li D. Chen (Natural Hazards, 2010)

TCF7L2 genetic variants and progression to diabetes in the Chinese population: pleiotropic effects on insulin secretion and insulin resistance - Yi-Cheng Chang; Yen-Feng Chiu; Larry Low-Tone Ho; Chih-Tai Ting; Kuang-Chung Shih; J. David Curb; Yii-Der Ida Chen; Hung-Yuan Li; Lee-Ming Chuang (Journal of Molecular Medicine, 2010)

Mechanical interactions of cuspal-coverage designs and cement thickness in a cusp-replacing ceramic premolar restoration: a finite element study - Yen-Hsiang Chang; Wen-Hsueng Lin; Wen-Chieh Kuo; Chia-Yu Chang; Chun-Li Lin (Medical & Biological Engineering & Computing, 2009)

Isolation and characterization of microsatellite loci in Pedicularis verticillata L. using PCR-based isolation of microsatellite arrays (PIMA) - Tsurng-Juhn Huang; Yi-Yen Chen; Yen-Ping Li; Cheng-Yu Hung; Tzen-Yuh Chiang; Chang-Hung Chou (Conservation Genetics, 2008)

Neuronal dysfunction of a long projecting multisynaptic pathway in response to methamphetamine using manganese-enhanced MRI - Yi-Hua Hsu; Chiao-Chi V. Chen; Anil Zechariah; Cecil C. Yen; Li-Chuan Yang; Chen Chang (Psychopharmacology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Diverse apoptotic pathways in enterovirus 71–infected cells - Shih-Cheng Chang; Jing-Yi Lin; Lily Yen-Cheng Lo; Mei-Ling Li; Shin-Ru Shih (Journal of NeuroVirology, 2004)

ESTABLISHMENT OF AN EFFICIENT METHOD TO QUANTIFY EMBRYO ATTACHMENT TO ENDOMETRIAL EPITHELIAL CELL MONOLAYERS - HSIN-YANG LI; SHENG-PING CHANG; CHIOU-CHUNG YUAN; HSIANG-TAI CHAO; HEUNG-TAT NG; YEN-JEN SUNG (In Vitro Cellular & Developmental Biology - Animal, 2002)